Enhanced Thermal And Tensile Behavior Of Mwcnt Reinforced Palm Oil Polyol-based Shape Memory Polyurethane - Aula Aqila Yusrizal; Tuti Katrina Abdullah; Ernie Suzana Ali; Sahrim Ahmad; Syazana Ahmad Zubir (King Saud University, 2024)
Indexed by WOS/Scopus/ERA